Intraosseous Anchorage of a Collagen Matrix Graft to Enhance Repair of Peroneus Brevis Tendon Degeneration. Issue 5 (October 2021) - Crafton, Jordan W.; Basile, Philip; Cook, Jeremy
Introduction: Chronic degeneration of the peroneus brevis tendon (PBT) at its insertion to the base of the fifth metatarsal is uncommon; however, when present it can be a challenge to treat. Repair of the PBT often requires tubularization with or without a peroneus longus tendon transfer. These repairs, however, may not provide resultant full muscle strength, especially if ostectomy of the fifth metatarsal base is required. We report outcomes following a novel technique for anatomic repair of degenerative PBT with intraosseous fifth metatarsal base fixation of a collagen matrix graft. Methods: Thirteen consecutive patients (14 procedures) with degeneration of PBT that underwent tendon repair augmented with collagen matrix graft from 2011 to 2019 were reviewed retrospectively. We present outcome data of these 13 patients that were followed for at least 12 months. Results: Muscle strength, complications, and patient-reported subjective outcomes were reported. There were 10 females and 3 males. Average age was 49.1 years, and average follow-up was 34.9 months. Muscle strength was reported at 5/5 to the PBT by the final follow-up for 92% of patients. There were minimal complications, 84.6% (11/13) of patients had no limitation in activity level, and 92% (12/13) would recommend this procedure to a friend. Conclusion: Outcomes for this novel repair technique for insertional degenerative PBT have never been reported before and show excellent results with long-term follow-up.